Synthesis of Fluorescent 1, 3‐Diarylpropynones by Carbonylative Alkynylation Reaction Using (Phosphine) (1, 2, 3‐triazol‐5‐ylidene)palladium Complexes as Catalysts. Issue 28 (6th October 2016) - Dasgupta, Ayan; Ramkumar, Venkatachalam; Sankararaman, Sethuraman
Abstract : The synthesis of a variety of 1, 3‐diarylpropynones that contain not only substituted phenyl groups but also fluorophoric 1‐pyrenyl, 3‐carbazolyl, and 1‐naphthyl groups was achieved in good to excellent yields by using a carbonylative alkynylation reaction in the presence of cis ‐(Tz)Pd(Cl)2 (PPh3 ) (Tz = 1, 2, 3‐triazol‐5‐ylidene) as a precatalyst under 1.0 atm of CO. Products resulting from competing Sonogashira coupling reactions, namely 1, 2‐diarylacetylenes, were not observed. The synthesized ynones exhibit fluorescence not only in solution but also in the solid state. The catalytically active palladium species was recovered and reused for up to three cycles by adsorbing the cis ‐(Tz)Pd(Cl)2 (PPh3 ) precatalyst onto silica gel and carrying out the reaction under heterogeneous conditions. Abstract : A Pd–N‐heterocyclic carbene (Pd–NHC) complex has been used as the catalyst in a carbonylative alkynylation reaction that afforded several fluorescent 1, 3‐diarylpropynones in high yields.